Supporting Graduate Students’ Critical Reading: A Relational Approach Through the Development of Digital Resources - Ronna Mosher; Alison Van Rosendaal (Canadian Journal for the Scholarship of Teaching and Learning)
Critical reading and discussion are intellectual practices both expected within and developed through graduate education. Maturing these practices requires pedagogical support, guidance, and authentic contexts in which critical thinking and language can be negotiated with others. This article documents a relational approach to developing digital resources to support novice graduate students’ critical engagement with scholarly literature in a context requiring the navigation of complex, interconnected dimensions of theory, practice, and professional identity. The article contributes to considerations of how graduate students develop critical reading capacities through a focus on the distinctive situated, relational, and intergenerational practices of educating attention. It conceptualizes critical reading as relational and provides a heuristic framework through which a relational intergenerational approach to supporting critical reading might be envisioned and enacted across disciplinary contexts.